PAST INTERNET SHAROITIDA MASOFAVIY ESP TA’LIMDA SUN’IY INTERNET ASOSIDAGI OG‘ZAKI NUTQ MASHQLARINI SAMARALI TASHKIL ETISH (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
This article addresses the issue of effectively organizing AI-based oral speaking exercises in distance ESP education under low-bandwidth internet conditions. The proposed methodological model enables students to develop context-appropriate, reflective, and communicative speaking skills through simplified AI tools. This approach enhances the quality of distance learning and fosters a new stage of digital pedagogy despite technical limitations.